Enhancing the Scope of Startup Activities through Eudaimonic Well-being: The Role of Mediation of Entrepreneurial Self-efficacy - Suwarno, Henky Lisan; Malinda, Maya; Jocelyn, Vania (International Review of Management and Marketing, 2026)
The paper examines the impact of eudaimonic well-being and entrepreneurial self-efficacy on the start-up activity of students in higher education. This research employs quantitative methods. Questionnaires were sent to 183 business students. Structural equation modeling empirically tests the idea. Eudaimonic well-being is positively related to entrepreneurial self-efficacy, such that individuals with higher levels of meaning, autonomy, and personal growth have more confidence about their entrepreneurial ability. Moreover, entrepreneurial self-efficacy is highly related to the operations of a startup. That is, self-confidence increases participation in entrepreneurial activities. However, eudaimonic well-being does not significantly influence startup activity. Importantly, entrepreneurial self-efficacy fully mediates the relationship between eudaimonic well-being and breadth of startup activity. The study adds to the entrepreneurial literature by demonstrating the role of psychological well-being in startup activity and the role of entrepreneurship education in well-being and self-efficacy. Policymakers and universities should develop treatments to improve students’ psychological well-being and entrepreneurial confidence to boost start-up activity.